Methoxy‐activated indole‐7‐carbohydrazides; synthesis, antioxidant, and anticancer properties. (7th September 2022) - Kandemir, Hakan; İzgi, Samet and Cınar, Irfan and Cebeci, Fatma and Dirican, Ebubekir and Saglam, Mehmet F. and Sengul, Ibrahim F.
Abstract: Indole has been known as a key heterocyclic motif in the development of new structures for both chemical and biological properties. In this current study, a new range of indole‐7‐carbohydrazides has been successfully synthesized starting from the readily available 3‐phenyl and 2, 3‐diphenyl 4, 6‐dimethoxyindoles. The structures of the novel compounds were confirmed by utilizing 1 H NMR, 13 C NMR, FT‐IR, high‐resolution mass spectrometry, and single crystal X‐ ray diffraction techniques. In addition, the indole‐7‐carbohydrazides showed promising antioxidant results in preliminary screens. Some of the new compounds generated from dimethoxy indoles were also screened for their anticancer activity against SH‐SHY5Y (human neuroblastoma), AGS (human gastric adenocarcinoma), and MDA‐MB‐231 (human breast adenocarcinoma) cell lines. The results revealed that the compound 12 was the promising candidate, showing cytotoxic effects on both neuroblastoma, stomach, and breast cancer cells. Abstract : Indole‐7‐carbohydrazides